3-Dimensional graphene-like structures and applications: general discussion - Backes, Claudia; Behera, Ranjan Kumar; Bellamy-Carter, Abigail; Bianco, Alberto; Caps, Valerie; Casiraghi, Cinzia; Chhowalla, Manish; Criado, Alejandro; Davies, Trevor; Ferrari, Andrea C.; Fornasaro, Stefano; Galembeck, Fernando; et al. (My University, 2021)
Stefano Fornasaro opened discussion of the paper by Manuela Melucci: Is the production scalable? Can you comment about reproducibility of the results? Manuela Melucci replied: We used commercial graphene oxide powder (Abalonyx) and commercial hollow fiber cartridges (Plasmart 25,
Keywords: None